The impact of Women Body Mass Index (BMI) on Fertility Outcome in Women Undergoing Assisted Reproductive Technologies (ART) - Mohammed, Balsam Kahtan (Medical Science Journal for Advance Research, 2025)
Background: The problem of overweight and obesity became increasingly recognized in the Iraqi community in various regions of the country during the last three decades because of changes in lifestyle and dietary habits. Significant proportions of women during reproductive life complain of obesity and overweight, which may negatively impact their reproductive potential. Aim of the study: The aim was to assess the impact of BMI on the outcomes of assisted reproductive technologies (ART), including intracytoplasmic injection “ICSI” and in vitro fertilization “IVF”. Patients and methods: The sample of infertile women was selected from the population of infertile women visiting the Higher Institute for Infertility Diagnosis and Assisted Reproduction Technologies, Baghdad - Iraq. The design of the study was retrospective observational single center cohort study. Data of women were obtained from the archive unit and included medical reports from January 2022 to January 2025. All enrolled women were subjected to the routine protocol of gonadotropin-releasing hormone (GnRH) antagonist. Results: Positive pregnancy tests were reported in 60 (21.1 %) cases of overweight/obese group compared to 116 (40.8 %) of normal weight group. There was a significant difference between groups (p < 0.001). The implantation rate among the overweight/obese group was found significantly less compared to the group of normal weight patients, being 49.24 ±9.23 % and 61.42 ±13.19 %, respectively (p < 0.001). Average number of embryos transplanted per woman were found with no significant variation across the research groups (p = 0.207). However, the mean of total number of retrieved oocytes per women was significantly less in overweight/obese group compared to normal weight group, being 4.23 ±2.94 and 5.79 ±2.41, respectively (p = 0.031), and no variation in fertilization rate between study groups (p = 0.297). Investigating the quality of embryos per women showed significant reduction in number of embryos with good quality in overweight/obese group compared to normal weight group, being 71.48 ±20.17 and 77.23 ±15.61, respectively (p = 0.031). Conclusion: The clinical positive pregnancy rate following ART can be significantly affected by the BMI of women with infertility. This was found to be attributed to the reduced rate of good quality embryos and lower implantation rate.